Voices of fire : reweaving the literary lei of Pele and Hi'iaka - Hoʻomanawanui, kuʻualoha (First peoples: new directions in indigenous studies., 2014)
This is a literary analysis of Pele and Hi'iaka literature from an Indigenous, specifically Hawaiian perspective, one inspired by the larger discussions of Indigenous literary nationalism by Native American scholars that seeks to add a Hawaiian voice to the conversation. It is also grounded in the Pacific and continuing efforts within Indigenous Studies programmes to negotiate their experiences and histories with settler colonialism and the misappropriations of their literatures that have been relegated to the realms of folklore, mythology, ethnography, and the postcolonial.